Potensi Ekstrak Solanum betaceum sebagai Agen Protektif Sel Leydig pada Mencit yang Dipapar Timbal Asetat - Anak Agung Istri Dalem Cinthya Riris; Reny I’tishom; Siti Khaerunnisa (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Lead exposure as environmental pollution can cause male reproductive problems. Provision of natural antioxidants can be an alternative solution to protect male reproductive function. This research was conducted to investigate the potential of Solanum betaceum extract as a protective agent for Leydig cells in mice exposed to lead acetate. The entire research process with a replication unit of 40 male mice. Mice were divided into five groups with each treatment given orally. The negative control group (K0) only gets aquadest for 35 days, the positive control group (K1) gets aquadest day 1-3, day 4-35 get lead acetate at a dose of 0.075 mg/kg BW/day, the treatment group (P1), (P2 ), and (P3) only given Solanum betaceum extract at day 1-3 with sequential doses of 100 mg/ kg BW /day, 200 mg/ kg BW /day, and 400 mg/ kg BW /day, then 4-35 days were given Solanum extract betaceum and after 1 hour given lead acetate. The results of this study indicate that there were significant differences between groups with p